EFFECT OF DRIED MORINGA OLEIFERA LEAVES ON GROWTH PERFORMANCE AND IMMUNE RESPONSE OF BROILERS - S. K. U. Hassan; A. Khalique; T. N. Pasha; A. W. Sahota (Journal of Animal and Plant Sciences, 2018)
Rising prices for oilseed meals and expected feed crises due to rapid increase in human and livestock population motivate nutritionists to look for good quality alternative protein sources. For this purpose, a study was conducted to evaluate the effects of Moringa oleifera leaf meal on growth performance and immune response in broilers. Total 300- day-old broiler chicks were divided into 15 replicates having 20 chicks each. After procuring and determining the chemical composition of Moringa oleifera leaf meal, five iso-nitrogenous and iso-caloric experimental diets were formulated. Group A was considered as control and given 0% MOLM, while, group B, C, D and E were fed on 5% MOLM, 10% MOLM, 15% MOLM and 20% MOLM, respectively. Data on feed intake, body weight were recorded on weekly basis and feed efficiency was calculated. The obtained data were subjected to one-way analysis of variance (ANOVA) and means were compared through Duncans Multiple Range( DMR) test. Results revealed that body weight of birds on diet 0%, 10% and 15% MOLM were significantly higher (Pd0.05) than others while, control group consumed significantly higher feed intake. On the other hand, 15% MOLM showed significantly improved mortality (%) and antibody titer against NDV while, feed efficiency was not affected by any treatment. It can be concluded that an inclusion level of 15% MOLM in diet improves the overall growth performance and immunity in broilers. protein comprised of significant quantities of all the
Keywords: Broilers; Moringa oleifera; Leaves; Growth performance; Immunity.